Sizing up competition with strigolactones: the case of pea plants - Bianca Bonato; Tom Bennett; Emanuele Cannizzo; Sara Avesani; Silvia Guerra; Umberto Castiello (Plant Signaling & Behavior)
Plants, though sessile, can detect and respond to their neighbors through chemical signals such as strigolactones (SLs). We investigated how SL synthesis and perception affect the climbing behavior of Pisum sativum by analyzing wild-type plants and two SL-related mutants—rms1–1 (SL-deficient) and rms3–1 (SL-insensitive) – grown either alone or paired with a plant of a different genotype but of the same genetic background. Using 3D kinematic analysis, we quantified the circumnutation and attachment dynamics. Our results show that social context significantly modulated climbing behavior. rms1–1 mutants, although unable to grasp the support, showed increased movement velocity in social conditions, suggesting enhanced exploratory behavior. In contrast, rms3–1 mutants exhibited slower, disoriented movements when paired, indicating impaired neighbor perception. Wild-type plants successfully grasped the support in all conditions but altered their behavior socially, increasing movement velocity with a more careful approaching phase. These results show that SL-mediated signaling, through both emission and perception, shapes context-dependent climbing strategies in pea plants.